UPAYA PENINGKATAN ANGKA PARTISIPASI PESERTA DIDIK MELALUI PROGRAM SOSIALISASI TERPADU - Sutopo Sutopo (Universitas Nahdlatul Ulama Blitar, 2016)
inwrought socialization program execution in this watchfulness achieve aim or target that appointed, because this program applications effectively proved give impact and influence enough significant towards entrant participation number enhanced educates at sd source country dumpyong 1 regency bondowoso. this program must then be carried out chronically so that government program in order to speed up obligatory successful learn education base 9 year complete